(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2025)
This study aims to explore the reality of business governance in tourism companies in the Kingdom of Saudi Arabia, focusing on the challenges they face and the opportunities available to them in light of Saudi Vision 2030. To achieve this goal, a quantitative approach was adopted, using a closed-ended questionnaire as the primary data collection tool. The sample included 160 participants working in tourism companies, representing various job levels, ages, and academic experience. The results revealed a growing awareness of the importance of governance, despite some challenges such as weak administrative competencies, a lack of awareness of governance concepts, and gaps in compliance with laws and regulations. The results also emphasized the role of Vision 2030, digital transformation, and government support as motivating factors for improving governance practices in this sector. Based on these findings, the study recommends the need to enhance training programs to raise administrative and functional awareness, develop legislative and regulatory frameworks, and focus on developing the technical infrastructure and financial reporting to enhance transparency and accountability. Furthermore, it recommends encouraging investment and strategic partnerships. Adopting these recommendations effectively contributes to enhancing the governance of aviation companies, positively impacting institutional performance and sustainable growth within the framework of Vision 2030.